Simultaneous determination of carcinogenic PAHs and levoglucosan bound to PM2.5 for assessment of health risk and pollution sources during a smoke haze period - Duangduean Thepnuan (2020)
© 2020 Elsevier Ltd Carcinogenic polycyclic aromatic hydrocarbons (cPAHs) in ambient PM2.5 and a specific molecular marker of biomass burning, levoglucosan, are used to investigate the influence on public health of biomass burning. In this work, we present an effective method for one-time analysis of cPAHs and levoglucosan by GC-MS without derivatization. The method was applied for the analysis of PM2.5 samples (64.3 ± 17.6 μg m−3, n = 57) collected during a smoke haze period in Chiang Mai, Thailand. Levoglucosan was analyzed by using both the developed method (GC-MS) and a reference method (HPAEC-PAD) for comparison. Its average concentration obtained from GC-MS (0.31 ± 0.21 μg m−3) was about 4 times less than the concentration obtained from the reference method (1.22 ± 0.76 μg m−3). Therefore, a correcting factor (CF = 4) was used as a multiplying factor, to obtain a comparative value (1.23 ± 0.86 μg m−3). The average concentration of cPAHs found in PM2.5 samples was 5.88 ± 1.97 ng m−3 with the highest value of 10.86 ng m−3 indicating medium to high cancer risk due to PAHs exposure when referring to values of toxicity equivalence and inhalation cancer risk. Diagnostic ratios of BaA/(BaA + CHR) (0.48 ± 0.04) and IND/(IND + BPER) (0.58 ± 0.04) and strong correlations between PM2.5, levoglucosan and cPAHs concentrations implied that the major source of air pollution in the study period was biomass burning. PM2.5 concentration as a pollution indicator was labelled as BB-low, BB-medium, BB-high or BB-extreme; <50, 50–75, 75–100 and > 100 μg m−3, respectively. The levoglucosan and cPAHs concentration during BB-extreme pollution was 4.3 times and 2.34 times, respectively, that during BB-low pollution, and the correlation coefficient (r) between the concentrations of levoglucosan and cPAHs was as high as 0.987, indicating that the more intense the burning of biomass, the higher the carcinogenic risk in the urban air.